Exploring the multilingual efficiency of urban online spaces: Implications for culture-centered design - Parmaxi, Antigoni; Nicolaou, Anna; Papadima-Sophocleous, Salomi; Boglou, Dimitrios (My University, 2016)
This paper builds up a picture of how multilingualism is supported in various aspects of urban online spaces. The main assumption of this study is that language is an indispensable element of culture; thus, understanding how a multilingual city facilitates multilingualism in terms of provision of and access to information, can deepen our understanding for supporting cross-cultural Human Computer Interaction (HCI). This study explores how multilingualism is supported in urban online spaces of Limassol, a location of increased inward migration and a city that holds a prolonged multilingual character. Data include manifestations of multilingualism or monolingualism in various online contexts, such as official websites and digital media. Findings demonstrate several aspects of multilingualism, as well as implemented policies and practices for promoting a multilingual online locus. As a result of the findings, suggestions for best practices for the online spaces of multilingual cities are put forward, as well as implications for cross-cultural HCI.
Keywords: Cross-cultural HCI; Interculturalism; Language; Language visibility; Multilingual online locus; Multilingualism